How minimalism and eco-consciousness shape the luxury fashion consumption - Kuznetsova, Kristina; Escobar Rios, Andrea; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores how minimalist luxury consumers in the Czech Republic adopt eco-conscious values and how these values shape their motivations, behaviours, and interactions with fashion brands. Drawing on qualitative interviews and the typology of minimalist consumers developed by Pangarkar et al. (2021), the study examines three consumer types: anti-consumption, voluntary simplicity, and inconspicuous minimalists, and their varying levels of sustainability engagement. Grounded in theories of minimalism, sustainable consumption, and conspicuous consumption, the findings reveal that sustainability can be both intentional and incidental and different in the degree of adoption. The thesis provides strategic implications for tailoring sustainability communication in the luxury fashion sector.
Vedoucí práce: Andrea Escobar Rios
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses